The Alternative Use of Islamic Endowment (Waqf) for Educational Desire Among Contemporary Northern Nigerian People: Penggunaan Alternatif Wakaf Islam untuk Kebutuhan Pendidikan di Kalangan Masyarakat Nigeria Utara Kontemporer - Muhammad, Adamu Abubakar; Ardo, Adam Muhammad; Aliyu, Shafa’at Ahmad; Muhammad, Zuwaira Jibril (Institut Agama Islam Negeri Kerinci, 2025)
Purpose: The feasibility and effective use of Waqf to bridge educational disparities in Northern Nigeria are investigated in this study. Design/methodology/approach: This study employs a qualitative methodology that includes a review of the literature, case studies, and expert interviews. These methods enable a thorough understanding of the challenges facing the local educational system as well as the contributions Waqf has made to the growth of education both historically and currently. Findings: Important insights into how Islamic endowment systems can reduce significant educational disparities in the region are obtained via the examination of relevant theoretical frameworks and empirical research. It highlights the potential uses of these endowments, which are motivated by religious beliefs, to fund education for disadvantaged pupils by examining Waqf models that have been successful in other Muslim nations. Research implications: Incorporating Waqf into educational funding would offer a workable, long-term way to reduce the negative consequences of the socioeconomic crisis and enhance educational goals in the region.